Case Report: A case of aural myiasis in an elderly bedridden patient with newly diagnosed Parkinson’s syndrome - Hao, Bingyan; Sun, Zhen; Peng, Caini; Zhong, Kaijie; Zhuo, Xianlu (Frontiers in Surgery, 2026)
Myiasis, an infestation of living vertebrates by dipteran larvae, is relatively uncommon in otorhinolaryngology. Chronic otitis media and other ear pathologies are significant predisposing factors. This article presents the case of an 89-year-old bedridden female patient who presented with right ear discharge and visible maggots. Following mastoid exploration and systemic antibiotic therapy, her clinical symptoms improved. This case highlights the increased susceptibility of elderly, bedridden patients to aural myiasis.